1996
DOI: 10.1007/bf02414636
|View full text |Cite
|
Sign up to set email alerts
|

Action of a high dose ofγ-rays on steatite ceramic

Abstract: Extensive material has been accumulated in the last few years on radiation defects in dielectric materials based on oxides. Most ceramic dielectrics consist of simple or complex oxide compounds which comprise the crystalline and glassy phases of a ceramic [1]. The formation of structural defects in oxide compounds, such as AI203, MgO, and SiO 2, under the action of 6~ ",/-rays is unlikely, but it is possible under some conditions. For example, structural defects have been observed to form during low-energy ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A characteristic feature of steatite ceramics in comparison with other ceramic materials is its high mechanical strength and low dielectric losses in some materials, for example, high-aluminous materials as GB-7, UV-46, muliticcorundum M-23 [3,4]. In [5][6][7][8], we showed that in steatite ceramics SK-1, when exposed to high-dose γradiation (>10 9 R), radiation defects with high thermal stability are formed, which are observed as peaks of thermo-luminescence (TL), EPR spectra (signal with g=2.0012) and diffuse reflectance spectra (DR) (λ=220 nm). These defects are formed mainly in the crystalline phase of magnesium meta-silicate MgSiO 3 (nonstoichiometric MgSiO 3 ) or surface layers of grains of the crystalline phase with a defective structure formed.…”
Section: Introductionmentioning
confidence: 99%
“…A characteristic feature of steatite ceramics in comparison with other ceramic materials is its high mechanical strength and low dielectric losses in some materials, for example, high-aluminous materials as GB-7, UV-46, muliticcorundum M-23 [3,4]. In [5][6][7][8], we showed that in steatite ceramics SK-1, when exposed to high-dose γradiation (>10 9 R), radiation defects with high thermal stability are formed, which are observed as peaks of thermo-luminescence (TL), EPR spectra (signal with g=2.0012) and diffuse reflectance spectra (DR) (λ=220 nm). These defects are formed mainly in the crystalline phase of magnesium meta-silicate MgSiO 3 (nonstoichiometric MgSiO 3 ) or surface layers of grains of the crystalline phase with a defective structure formed.…”
Section: Introductionmentioning
confidence: 99%